Analysis of the Effect of Nicotine on Brain Activity and Function Using FMRI: Implications for Cigarette Dependence - Saefullah, Rifki; Hidayana, Rizki; Rusyn, Volodymyr (Communication in Research and Publications (CRP), 2024)
This study examines the effect of nicotine, the main compound in cigarettes, on brain activity and function using functional Magnetic Resonance Imaging (fMRI). Nicotine influences the release of neurotransmitters such as dopamine and serotonin, which affect various aspects of life, including learning, memory, alertness, and emotional balance. Dependence on nicotine can cause withdrawal symptoms, such as anxiety, depression, and sleep disorders. Neurological research shows differences in brain activity in smokers and non-smokers, especially in the ventral (rostral anterior cingulate cortex, insula, opercular, and occipital gyrus) and dorsal (dorsal medial/lateral prefrontal cortex and dorsal anterior cingulate cortex) areas. Brain disorders are also associated with psychological disorders such as anxiety, depression and compulsive behavior. Apart from that, nicotine use can also affect the dopamine and serotonin systems, resulting in sleep disorders and emotional disorders in cigarette addicts.